Does physical fitness enhance lung function in children and young adults?. Issue 2 (1st February 2018) - Hancox, Robert J.; Rasmussen, Finn
Although physical activity is important for lung health, it is unclear whether physical fitness influences lung function. We investigated associations between lung function and fitness in two population-based cohort studies of children and young adults. Aerobic fitness was measured using a maximal cycle ergometer test at ages 9, 15, 21 and 29 years in Odense, Denmark and using a submaximal cycle test at ages 15, 26, 32 and 38 years in Dunedin, New Zealand. Aerobic fitness was positively associated with forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) in cross-sectional analyses at all ages in both cohorts, independently of height, weight, sex, asthma and smoking. Each standard deviation difference in fitness was associated with 2–3% predicted higher values of FEV1 and FVC. Improvements in fitness during childhood and adolescence were associated with growth in lung volumes in longitudinal analyses. These associations tended to be stronger in males than females. No longitudinal associations were found after peak adult lung function had been attained. Fitness was not significantly associated with FEV1 /FVC ratios. Aerobic fitness is positively associated with lung volumes. Improving fitness during childhood and adolescence is associated with greater adult lung volumes, but not with airway calibre. Increasing physical fitness during childhood and adolescence is associated with greater growth in lung volumes http://ow.ly/UubB30gh0mG